(untitled) (Revista Científica Tecnológica - ISSN: 2708-7093, 2018)
The influence of eight productive agricultural sectors on the economic integration of five Central American countries was analyzed. The sectors included are rice, beans, corn, sorghum, bananas, coffee, sugar cane, and beef. The countries are Costa Rica, El Salvador, Guatemala, Honduras, and Nicaragua. A theoretical framework of game theory is used to find Nash equilibrium solutions for a set of trade negotiation scenarios. The payments of the political preferences function (PPF) are used for the trade liberalization scenarios under analysis. The payments were estimated with the MISS model. The nominal protection coefficient (NPC) is used as the main criterion for the exchange (commercial opening). The following scenarios were analyzed: status quo (SQ) or zero percent (0%) reduction in protection, 25%, 50%, 75%, and 100% (full commercial opening or free trade (FT)) of reduction in the protection. Four simulations were modeled. In simulation 1 it is assumed that all sectors have, in the PPF, a specific weight equal to one, which indicates that all sectors have the same importance from the point of view of the government. In the second simulation all the specific weights differ from being equal to one, that is, the government assigns different degrees of importance and some sectors are considered more important in relation to other sectors and to the government itself. The third and fourth simulations are the same as the first and second simulations, but the exchange rate of the currency is reduced by 5% The results show that any of the countries individually would accept 100% in the reductions of the protection (free trade, FT) when the rest of the other countries, as a block, reduce the protection by 50%. This indicates that Central American countries would probably accept a trade opening rather than a deeper form of economic integration. The analyzed sectors do not affect the commercial opening in an adverse way. This study suggests that the use of game theory is an appropriate framework for analyzing economic integration in Central America.